Method for producing quinoline and the use thereof - Abdullah, Siti Nor Akmar; Syd Ali, Nusaibah; Meon, Sariah; Zakaria, Muhamad Pauzi; Abu Seman, Idris (2011)
The present invention relates to a method for preparing a quinoline compound from infected oil palm comprising the steps of; preparing an infected oil palm with Ganoderma boninense; grounding a root sample and obtaining a fine powder; mixing the fine powder with an adequate amount of anhydrous sodium sulphate and obtaining a solution; adding methanol into the solution and obtaining a mixture; filtering the mixture; and drying the mixture. The product produced from the method is usable as an antifungal for oil palm or coconut.